Continuous blood pressure measurement using the pulse transit time: Comparison to intra-arterial measurement. (August 2015) - Patzak, Andreas; Mendoza, Yuri; Gesche, Heiko; Konermann, Martin
Abstract Continuous blood pressure (BP) measurement allows the investigation of transient changes in BP and thus may give insights into mechanisms of BP control. We validated a continuous, non-invasive BP measurement based on the pulse transit time (PTT), i.e. BPPTT, by comparing it with the intra-arterial BP (BPi.a.) measurement. Twelve subjects (five females and seven males) were included. BPi.a. was obtained from the radial artery using a system from ReCor Medical. Systolic and diastolic BP were calculated using the PTT (BPPTT, SOMNOscreen™). PTT was determined from the electrocardiogram and the peripheral pulse wave. The BP was modulated by application of increasing doses of dobutamine (5, 10, 20 μg/kg body mass). Systolic BPPTT and systolic BPi.a. correlated significantly (R = 0.94). The limits of agreement in the Bland—Altman plot were ± 19 mmHg; the mean values differed by 1 mmHg. The correlation coefficient for the diastolic BP measurements was R = 0.42. The limits of agreement in the Bland—Altman plot were ± 18 mmHg, with a mean difference of 5 mmHg in favour of the BPPTT. The study demonstrates a significant correlation between the measurement methods for systolic BP. The results encourage the application of PTT-based BP measurement for the evaluation of BP dynamics and pathological BP changes.